Legal Certainty of Physical Dominion by The Community Over Ex Eigendom Verponding Land - Azkiya Kamila Rosadi; Yani Pujiwati; Betty Rubiati (The Kalimantan Social Studies Journal, 2025)
The role of land in national development is increasingly important to meet the needs for housing and commercial activities, requiring legal certainty through clear, comprehensive, and written legal instruments. The enactment of the Basic Agrarian Law (UUPA) abolished the concept of land rights under Western law. However, there are still lands with the legal basis of eigendom verponding that have not been converted, and the land rights holders or their heirs continue to claim ownership. The research method used in this study is normative juridical. Data collection techniques include document studies and interviews, with qualitative juridical. The result of the research discussion shows that the Supreme Court decision No. 109/PK/Pdt/2022, which favored the Muller family, indicates legal uncertainty as it is inconsistent with regulations governing former Western rights land, which should be controlled by the state and prioritize those who have physical dominion of the land.